Use of first metatarsophalangeal joint chondroplasty with the autologous matrix-induced chondrogenesis technique for the treatment of patients with hallux rigidus: immediate results - M. R. Nurmukhametov; M. A. Makarov; E. I. Byalik; V. E. Byalik; V. A. Nesterenko (Научно-практическая ревматология, 2020)
Currently, there are a lot of different surgical treatments for hallux rigidus, such as cheilectomy; first metatarsal osteotomies, hemiarthroplasty, arthroplastry and arthrodesis of the first metatarsophalangeal joint (MTPJ), and all of them have both advantages and disadvantages. To date, there is no single approach to choosing a method of surgical treatment of hallux rigidus. The autologous matrix-induced chondrogenesis (AMIC) technique is known to be quite successfully used for the treatment of osteochondral defects in the knee, hip, and ankle joints.Objective: to study the immediate results of first MTPJ chondroplasty using the AMIC technique in patients with hallux rigidus.Subjects and methods. As of now, MTPJ chondroplasty using the AMIC technique has been performed at the Nasonova Research Institute of Rheumatology in the first 9 patients with hallux rigidus. The surgery was made on both sides in one patient; there were accordingly a total of 10 above operations. The patients' mean age was 42.2+19.5 (range 20—71) years. During the examination, the investigators determined the range of motion in the first MTPJ, the intensity of pain on a visual analogue scale (VAS); foot status according to the American Orthopedic Foot and Ankle Society (AOFAS) scale; as well as the foot function index (FFI) and the functional condition of the foot and ankle (FA) joints according to VAS-FA. Prior to surgery, all the patients experienced significantly restricted motions in the first MTPJ. The median range of motion in the first MTPJ was 20°; Pain intensity was 70 mm; the AOFAS score was 52; FFI — 6.4; the VAS-FA — 4.1. First MTPJ chondroplasty was performed according to the AMIC technique using the Chondro-Gide and Aesculap Novocart Basic collagen matrices. The results of surgical treatment were assessed at 3, 6, and 12 months postoperatively.Results and discussion. Just 3 months after surgery, there was a pronounced significant reduction in first MTPJ pain. Its median decreased from 70 to 27.5         mm. After 6 months, there were also positive changes; the median pain was 10 mm. It remained at a level of 10 mm by the end of the first year of the observation. The median AOFAS scores increased from 52 to 78.5 and 90 at 3 and 6 months after surgery, respectively, and remained at the same level at 12 months. The median FFI decreased from 6.4 to 2.3, 1.1, and 0.8 at 3, 6, and 12 months following chondroplasty, respectively. The median VAS-FA scores were 8.1, 9.3, and 9.6 at 3, 6, and 12 months after chondroplasty. At 3 months postoperatively, the range of first MTPJ motion also increased significantly: its median rose from 20° to 60°; it was 65° at 6 months and increased to 67.5° at 12 months. First MTPJ chondroplasty with the AMIC technique in these patients resulted in positive changes that were maximal at 3 months after the surgery: the median pain decreased by 42.5      mm; AOFAS, FFI, and VAS-FA scores increased by 26.5, 2.1, and 4.0, respectively. Of great importance is also the increase in first MTPJ motion range, the median of which rose by 40° at 3 moths. The positive changes also persisted 6 months postoperatively. During this period, there was a further decrease in the median pain by 17.5 mm and increases in the median AOFAS, FFI, and VAS-FA scores by 12.5, 1.2, and 1.2, respectively. At 12 months of the follow up, the achieved improvement remained; however, the number of observations at this stage does not allow for adequate statistical analysis.Conclusion. The immediate results of the performed operations showed that first MTPJ chondroplasty using a collagen matrix can be a rather effective surgical treatment that makes it possible to relieve pain and to significantly improve quality of life in patients with hallux rigidus. A more complete evaluation of the efficiency of first MTPJ chondroplasty using the AMIC technique will be provided by studying the medium-term and long-term outcomes of the surgery.